Optimization of mechanical properties, biocorrosion properties and antibacterial properties of wrought Ti-3Cu alloy by heat treatment - Mianmian Bao; Ying Liu; Xiaoyan Wang; Lei Yang; Shengyi Li; Jing Ren; Gaowu Qin; Erlin Zhang (Bioactive Materials, 2018)
Previous study has shown that Ti-3Cu alloy shows good antibacterial properties (>90% antibacterial rate), but the mechanical properties still need to be improved. In this paper, a series of heat-treatment processes were selected to adjust the microstructure in order to optimize the properties of Ti-3Cu alloy. Microstructure, mechanical properties, biocorrosion properties and antibacterial properties of wrought Ti-3Cu alloy at different conditions was systematically investigated by X-ray diffraction, optical microscope, scanning electron microscope, transmission electron microscopy, electrochemical measurements, tensile test, fatigue test and antibacterial test. Heat treatment could significantly improve the mechanical properties, corrosion resistance and antibacterial rate due to the redistribution of copper elements and precipitation of Ti2Cu phase. Solid solution treatment increased the yield strength from 400 to 740 MPa and improved the antibacterial rate from 33% to 65.2% while aging treatment enhanced the yield strength to 800–850 MPa and antibacterial rate (>91.32%). It was demonstrated that homogeneous distribution and fine Ti2Cu phase plays a very important role in mechanical properties, corrosion resistance and antibacterial properties.